Proposta metodológica de avaliação do grau de satisfação de população de área urbana. Estudo de caso: bairro Antenor Garcia, município de São Carlos, SP - Gaspar, Waldir José (2006)
Although public politics determine priorities in the evaluation of the development and in the accomplishment of the human well-being, this work considers the possibility in evaluating the degree of satisfaction of the population, based on the priorities and indicators from the population perspective. The subject assumes extreme outlines when related to the correct use of the public resources and of the failure of municipal programs destined to the residents mainly inserted in the urban outlying space. Evaluation of the degree of satisfaction of the population comes as a strategy to evaluate the impacts produced by the investments - publics or private - in projects of social development. In this study the population of a recent outlying neighborhood (Social Division into lots Antenor Garcia), of the city of São Carlos, SP, with approximately five thousand inhabitants, was considered. With base in the answers for a single open and synthetic question: What does you like and unlike in the neighborhood in what you live? ", a questionnaire with seventy six subjects contained in six variables: Health; Social; Education and Recreation; Safety; Habitation and Environment; and Transports, was elaborated. As for the form of the scale of the questionnaire it was adopted of the type LIKERT, with referencial of OSGOOD, with answers induced for Totally Disagree (DT); "Disagree Partially" (DP); "Without Opinion" (SO); "Agree Partially" (CP) or Totally Agree (CT). The consistence measures among the correlations were made with base in the coefficient Alpha of CRONBACH, that resulted in: medium to high correlation (>0.66) for internal analysis to the variables; and medium correlation (0.46), for inter-variable analysis - function of the correlated aspects (e.g. Safety versus Health). The variable Transports were the one that presented smaller degree of satisfaction - probably due to distance of the neighborhood downtown of São Carlos. While the item public illumination which belongs to the variable Habitation and Environment was the one with best degree of satisfaction - probably due to the appeal of some of the aspects of safety manifested by the habitants of this suburb. One expects that this methodology comes to contribute to deal with the conflict between the interests of the population and the urban planning, in way to understand and to assist the real needs of those populations, in the application of the public resources.